The potential use of e-learning to support teaching, learning and assessment in Information Systems at Walter Sisulu University - Sabalele, Tabisa (Rhodes University, Faculty of Education, Department of Education, 2008)
This research is an investigation of the potential means to make the Information Systems (IS) course more accessible to Walter Sisulu University (WSU) students. As some IS students at this institution are unable to attend classes on a regular basis, this study aims to establish if and how the WSU Accounting Department (which offers the IS course) could use e-Iearning to support the teaching, learning and assessment of IS. This qualitative study was approached from an interpretive perspective. The study has undergone one cycle of an action research approach. The methods used in the study include surveys, an expert review and focus group interviews. The data was elicited from participants using questionnaires and an interview schedule. A staff questionnaire was used to elicit information from IS staff from four contact universities in South Africa to determine their experience of using Information and Communication Technology (ICT) for e-learning in an IS course. A student questionnaire was used to determine the WSU IS students' reasons for absenteeism, their learning needs, and their current computer access and skills. Data from both of these surveys informed the development of the WSU IS pilot website. An expert review questionnaire ascertained the subject expert's opinions about the newly developed WSU IS pilot website. The website was found to be of good quality with respect to the four aspects that Harvey and Green (J 993 cited in Lomas 2002) use to define quality. Some modifications were made to the WSU IS pilot website as a result of the expert's comments. After the website was used by the IS students, two focus group interviews were conducted to determine the students' perceptions of the value of the website. The data was analyzed, interpreted and linked to the literature surveyed. The main findings indicate that the WSU IS pilot website could be part of a more globalised higher education offering than the paper-based IS course offered before. However, the staff and the student surveys revealed that ICT has opened the gap in equity at the higher education institutions, highlighting that access to a university does not mean equal access to lectures and computers. The WSU IS pilot website endeavoured to capitalise on students' physical access to computers by supporting epistemological access to the curriculum, by encouraging them to exercise control over their learning. This study has ideally enabled the Accounting Department to deliver its services to students and this in turn will hopefully help WSU retain its part-time students and improve the student pass rates.
Keywords: Walter Sisulu University for Technology & Science; Information technology -- Study and teaching (Higher) -- South Africa; Educational technology -- South Africa; Education, Higher -- Computer-assisted instruction; Universities and colleges -- Computer networking; Computer-assisted instruction -- South Africa; Internet in higher education; Educational tests and measurements